2021
DOI: 10.1097/jnc.0000000000000232
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Cognitive Ability and HIV: A Review of the State of the Nursing Science

Abstract: Neurocognitive problems have been endemic to the HIV epidemic since its beginning. Four decades later, these problems persist, but currently, they are attributed to HIV-induced inflammation, the long-term effects of combination antiretroviral therapy, lifestyle (i.e., physical activity, drug use), psychiatric, and age-associated comorbidities (i.e., heart disease, hypertension). In many cases, persons living with HIV (PLWH) may develop cognitive problems as a function of accelerated or accentuated normal aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 114 publications
3
28
0
1
Order By: Relevance
“…Among other factors, lack of licensure may be attributed to PLWH's socioeconomic constraints (Vance et al, 2015) given that most of our sample had annual household incomes of less than $20,000, an assumption supported by the significant association found between education and income with licensure status, as well as several other driving variables. This association resonates with the complexities (e.g., poverty, limited social resources) faced by PLWH that may be especially exacerbated among African Americans in the Deep South where this study was conducted (Quinn et al, 2017;Reif et al, 2017); in fact, such health disparities that may comprise brain health may account for the higher prevalence (58%) of cognitive impairment observed in this study, compared to the normal range observed in the literature between 30 and 50% of those with HIV (Waldrop et al, 2021). Other demographic associations with valid licensure included white race and older age.…”
Section: Discussionsupporting
confidence: 75%
“…Among other factors, lack of licensure may be attributed to PLWH's socioeconomic constraints (Vance et al, 2015) given that most of our sample had annual household incomes of less than $20,000, an assumption supported by the significant association found between education and income with licensure status, as well as several other driving variables. This association resonates with the complexities (e.g., poverty, limited social resources) faced by PLWH that may be especially exacerbated among African Americans in the Deep South where this study was conducted (Quinn et al, 2017;Reif et al, 2017); in fact, such health disparities that may comprise brain health may account for the higher prevalence (58%) of cognitive impairment observed in this study, compared to the normal range observed in the literature between 30 and 50% of those with HIV (Waldrop et al, 2021). Other demographic associations with valid licensure included white race and older age.…”
Section: Discussionsupporting
confidence: 75%
“…Still, the prevalence of mild-to-moderate cognitive impairments (e.g., HIV-associated neurocognitive disorder [HAND]) remains high, affecting between 30% to 50% of PLWH. HAND is defined as a collection of cognitive symptoms whereby an individual scores 1 or more SD s below the norm-based (age, education, sex, and race) mean on cognitive performance tests in two or more cognitive domains (e.g., executive functioning, verbal memory, and psychomotor functioning; Waldrop et al, 2021 ). HAND can emerge from a variety of synergistic factors, including age-related brain changes, comorbid physical conditions, psychiatric conditions, and social factors (e.g., stigma and social withdrawal).…”
Section: Neurohiv and Cognitionmentioning
confidence: 99%
“…Second, the pandemic has been a highly stressful time, with many individuals concerned about becoming ill, finances, caregiving for others, and experiencing new roles. As with primary inflammation, such stress can increase cortisol production through overactivation of the HPA axis, resulting in both systemic and neuroinflammation ( Cody & Vance, 2016 ; Waldrop et al, 2021 ).…”
Section: Neurocovid and Cognitionmentioning
confidence: 99%
See 2 more Smart Citations